Strategi Pemberdayaan Masyarakat Islam Melalui Pendidikan Dan Ekonomi Berbasis Masjid Di Desa Widasari - Shobani (CV Edujavare Publishing, 2024)
The aim of this research is to see how Widasari Village uses the mosque as a center for activities and education to encourage its Islamic community. Widasari Village uses a holistic approach to encourage community, integrating educational, economic and social elements. To increase the community's economic independence, this empowerment program includes religious education, productive economic training, and productive use of zakat and alms. This research uses a qualitative approach, which collects data through observation, interviews and document study. The research results show that mosque-based empowerment programs can increase economic independence, strengthen social solidarity, and increase religious awareness among the community. However, there are several challenges faced, such as a lack of funding for empowerment programs, low levels of formal community education, and a lack of collective awareness. By strengthening collaboration between mosques, government and society, this research suggests that empowerment programs should be prioritized and supported by various parties.